Immunohistochemical biomarker validation in highly selective needle biopsy microarrays derived from mpMRI‐characterized prostates. Issue 16 (2nd August 2018) - Olivier, Jonathan; Stavrinides, Vasilis; Kay, Jonathan; Freeman, Alex; Pye, Hayley; Ahmed, Zeba; Carmona Echeverria, Lina; Heavey, Susan; Simmons, Lucy A. M.; Kanthabalan, Abi; Arya, Manit; Briggs, Tim; et al.
Abstract : Introduction: Diagnosing prostate cancer routinely involves tissue biopsy and increasingly image guided biopsy using multiparametric MRI (mpMRI). Excess tissue after diagnosis can be used for research to improve the diagnostic pathway and the vertical assembly of prostate needle biopsy cores into tissue microarrays (TMAs) allows the parallel immunohistochemical (IHC) validation of cancer biomarkers in routine diagnostic specimens. However, tissue within a biopsy core is often heterogeneous and cancer is not uniformly present, resulting in needle biopsy TMAs that suffer from highly variable cancer detection rates that complicate parallel biomarker validation. Materials and Methods: The prostate cores with the highest tumor burden (in terms of Gleason score and/or maximum cancer core length) were obtained from 249 patients in the PICTURE trial who underwent transperineal template prostate mapping (TPM) biopsy at 5 mm intervals preceded by mpMRI. From each core, 2 mm segments containing tumor or benign tissue (as assessed on H&E pathology) were selected, excised and embedded vertically into a new TMA block. TMA sections were then IHC‐stained for the routinely used prostate cancer biomarkers PSA, PSMA, AMACR, p63, and MSMB and assessed using the h‐score method. H‐scores in patient matched malignant and benign tissue were correlated with the Gleason grade of the original core and the MRI Likert score for the sampled prostate area. Results: A total of 2240 TMA cores were stained and IHC h‐scores were assigned to 1790. There was a statistically significant difference in h‐scores between patient matched malignant and adjacent benign tissue that is independent of Likert score. There was no association between the h‐scores and Gleason grade or Likert score within each of the benign or malignant groups. Conclusion: The construction of highly selective TMAs from prostate needle biopsy cores is possible. IHC data obtained through this method are highly reliable and can be correlated with imaging. IHC expression patterns for PSA, PSMA, AMACR, p63, and MSMB are distinct in malignant and adjacent benign tissue but did not correlate with mpMRI Likert score.